Performance of the LHCb RICH detector at the LHC - Adinolfi, M; Rinella, G; Albrecht, E; Bellunato, T; Benson, S; Blake, T; Blanks, C; Brisbane, S; Brook, N; Calvi, M; Cameron, B; Cardinale, R; et al. (2013)
The LHCb experiment has been taking data at the Large Hadron Collider (LHC) at CERN since the end of 2009. One of its key detector components is the Ring-Imaging Cherenkov (RICH) system. This provides charged particle identification over a wide momentum range, from 2-100 GeV/c. The operation and control, software, and online monitoring of the RICH system are described. The particle identification performance is presented, as measured using data from the LHC. Excellent separation of hadronic particle types (π, K, p) is achieved. © 2013 CERN for the benefit of the LHCb collaboration.